Study of Mean Diameter of Middle Cerebellar Peduncle in Bangladeshi Cadaver - Haque, AQM Ataul; Khalil, Muhsin; Sultana, Seheli Zannat; Mannan, Sabina; Rahman, Md Mahbubur; Hossain, Muazzem; Ara, Anjuman; Begum, Taslima; Choudhury, Shilpi; Haque, Nazia (Community Based Medical Journal, 2016)
This cross sectional descriptive study was done by using nonprobability sampling technique and performed by examining 63 (sixty three) cerebellum. Out of them 40 postmortem human cerebellum collected from Bangladeshi cadavers of both sexes (male 25 and female 15) age ranging from 5 to 60 years and 23 cerebellums from caesarian section of intrauterine death cases of both sexes (male 14 and female 9) age ranging from 34 wks to 42 wks. of gestation. Specimens were collected from dead bodies autopsied on different dates from April 2009 to September 2009 at the autopsy laboratory of department of Forensic Medicine and prenatal cases from Gynaecology and Obstetrics Department of Mymensingh Medical College, Mymensingh. The collected specimens were grouped into three age groups like Group A (28 to 42 weeks of gestation), Group B (5 to 30 years) and Group C (31 to 60 years) and, two sex groups (male and female). The diameters of the middle cerebellar peduncles of both cerebellar hemispheres were measured by using slide calipers and expressed in millimeter (mm). The measurement was taken after fixation into 10% formal saline. The mean (± SD) diameter of right middle cerebellar peduncle was in Group A 6.70 ± 0.95, B 11.57 ± 2.57 and C 11.80 ± 1.40 mm respectively and it was also observed that mean diameter of right middle cerebellar peduncle increased with age. The mean (± SD) diameter of left middle cerebellar peduncle was in Group A 6.44 ± 0.83, B 11.35 ± 2.50 and C 11.40 ± 1.23 mm respectively and it was also observed that mean diameter of left middle cerebellar peduncle increased with age. CBMJ 2016 January: Vol. 05 No. 01 P: 14-19